Using participatory processes in Senegal, Guatemala and Kenya to develop gender-sensitive climate information services - Vyas, Shalika; Giraldo Mendez, Diana (CGIAR System Organization, 2024)
The digital divide is a significant barrier to providing effective CIS. In Kenya, it is estimated that 30% of rural livestock farmers lack the digital literacy needed to access or understand climate advisories. People in rural areas in Guatemala show similar low digital literacy levels, often falling below 40% literacy in using digital tools for agriculture, especially in marginalized Indigenous communities. For women, the challenge is even greater, and in Senegal, they are 25% less likely to have access to mobile phones, limiting their ability to receive crucial climate information. Another barrier is trust. Climate information needs to come from sources that farmers trust—like the local radio, community elders, or fellow farmers— not only meteorological agencies. It is not just a matter of disseminating accurate information; it’s about ensuring that the information is provided in a way that resonates with both men and women farmers. The Livestock and Climate Initiative tackled these challenges by bringing together national meteorological services, socially inclusive CIS, and local knowledge systems. Based on evidence of how best to help farmers, the Initiative is transforming how livestock producers receive and use climate information. We are building partnerships, translating science into actionable advisories using local knowledge and ensuring that even the most marginalized communities can understand and respond to climate risks facing their livestock. This Brief documents the pathways taken to reach our outcomes.